Colonization of methicillin-resistant staphylococcus aureus (MRSA) on neckties, headcarves and identification badges among medical students in UPM 2013 - Nurhidayah Zainuddin
Background: Methicilin-resistant Staphylococcus Aureus orMRSA is a staphylococcus bacteria strain that can be transmitted through various ways and can cause life-threatening condition if infected to immunocompromised patients in healthcare setting. Objective: The aim of this study is to detect the prevalence of colonization of MRSA on neckties, headscarves and ID Badges among medical students in UPM. Methods: A cross-sectional study was conducted. This study involves 256 medical students comprising of 153 and 103 pre-clinical and clinical students respectively. A validated questionnaire was use to collect the data and samples swab were collected by swabbing neckties, headscarves or identification badges. Results: Out of 433 samples taken, 40 swabs (9.24%) were positive for S. aureus. From this 40, five (12.5%) isolates were MRSA. Out of these five, one culture was isolated from headscarf of pre-clinical student; one culture was isolated from necktie of clinical students while the remaining three were isolated from identification badges of clinical students. There was no significant association between age, gender, ethnicity and phase of medical students with colonization of MRSA (p>0.05). There was significant association between knowledge score on hand hygiene practice and phase of medical students. Conclusion: MRSA colonies were presences on neckties, headscarves and identification badges. However there was no significant difference between presence of this and phase of medical students. There was significant association between knowledge score on hand hygiene practice and phase of medical students. However, there was no association between colonization ofMRSA and age, gender, ethnicity. Keywords: Staphylococcus Aureus, MRSA, colonization, neckties, headscarves, identification badges, medical students